Democracy, citizen support, and new generations in the face of democratic backsliding in Central America - Pignataro, Adrián (2021)
Facing the Bicentennial of Independence, this article examines the development of the political regimes in Central America after the transitions of the eighties. First, we observe that all countries, except for Costa Rica, experience processes of gradual erosion, in various conceptual dimensions of democracy. Second, citizen support for the political system and democracy has decreased in all countries. Finally, we find that political and democratic support are lower among young people. These levels of support are linked to perceptions of insecurity and material privation. The changes occur in a context of party fragmentation, the rise of authoritarian leaders, and the absence of state responses to demands for greater equality and economic well-being.